Effects of the revised WIC food package on women's and children's health: a quasi-experimental study - Alice Guan; Akansha Batra; Rita Hamad (BMC, 2022)
Abstract Background: The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) was revised in 2009 to be more congruent with national dietary guidelines. There is limited research examining effects of the revision on women's and children's health. The objective of this study was to evaluate whether the revised WIC food package was associated with various indicators of physical and mental health for women and children. Methods: We used 1998-2017 waves of the National Health Interview Survey (N = 81,771 women and 27,780 children) to estimate effects of the revised WIC food package on indicators of health for both women (self-reported health and body mass index) and children (anemia, mental health, and parent-reported health). We used difference-in-differences analysis, a quasi-experimental technique that assessed pre-post differences in outcomes among WIC-recipients while "differencing out" the secular underlying trends among a control group of non-recipients. Results: For all outcomes evaluated for women and children, we were unable to rule out the null hypothesis that there was no effect of receiving the revised WIC food package. These findings were confirmed across several secondary analyses conducted to assess heterogeneity of effects and robustness of results. Conclusion: While we did not find effects of the revised WIC food package on downstream health indicators, studies using similarly robust methods in other datasets have found shorter-term effects on more proximal outcomes related to diet and nutrition. Effects of the modest WIC revisions may be less impactful on longer-term indicators of health, and future studies should examine the larger COVID-19-era expansion.